Rating of perceived exertion in continuous sports: a scoping review with evidence gap map - Torres, G.; Maia, F.; Nakamura, F. Y.; Neiva, H. P.; Sousa, A. (Frontiers in Sports and Active Living, 2025)
Introduction: Rating of perceived exertion (RPE) is widely used for assessing training load in sports due to its validity, simplicity, and utility. Despite its broad application, the diverse contexts and methodologies in which it is used warrant a comprehensive review of the existing evidence.